2017
DOI: 10.1016/j.worlddev.2016.11.005
|View full text |Cite
|
Sign up to set email alerts
|

The Tragedy of the Grabbed Commons: Coercion and Dispossession in the Global Land Rush

Abstract: Rural populations around the world rely on small-scale farming and other uses of land and natural resources, which are often governed by customary, traditional, and indigenous systems of common property. In recent years, large-scale land acquisitions have drastically expanded; it is unclear whether the commons are a preferential target of these acquisitions. Here we argue that the contemporary global “land rush” could be happening at the expense of common-property systems around the world. While there is evide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
130
0
4

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 248 publications
(136 citation statements)
references
References 61 publications
2
130
0
4
Order By: Relevance
“…This study demonstrated how the medium-scale forestland appropriations have created in situ displacement and become detrimental to local livelihoods and forest conservation in a way that recalls criticisms of the large-and mega-scale international land grabs in the peripheral lowlands of Ethiopia and elsewhere in the global south over the past ten years (e.g., [3,5,7,10,12,19]). Local farmers' low interest in taking up the alternative livelihood option (i.e., low-paying temporary jobs), the absence of technology transfers from the companies to the farmers and the inability of earlier established companies to contribute to Ethiopia's foreign currency earnings through coffee exports coupled with the aggravated deforestation from the local farmers' efforts to secure access through more intensive use following the forestland transfers to private companies highlight the overall failure to achieve the objectives of transferring forestland to private companies.…”
Section: Conclusion and Way Forwardmentioning
confidence: 60%
See 4 more Smart Citations
“…This study demonstrated how the medium-scale forestland appropriations have created in situ displacement and become detrimental to local livelihoods and forest conservation in a way that recalls criticisms of the large-and mega-scale international land grabs in the peripheral lowlands of Ethiopia and elsewhere in the global south over the past ten years (e.g., [3,5,7,10,12,19]). Local farmers' low interest in taking up the alternative livelihood option (i.e., low-paying temporary jobs), the absence of technology transfers from the companies to the farmers and the inability of earlier established companies to contribute to Ethiopia's foreign currency earnings through coffee exports coupled with the aggravated deforestation from the local farmers' efforts to secure access through more intensive use following the forestland transfers to private companies highlight the overall failure to achieve the objectives of transferring forestland to private companies.…”
Section: Conclusion and Way Forwardmentioning
confidence: 60%
“…Due to weak legal recognition of customary rights to commons, forest and pasturelands have historically been and still are easy prey to dispossessions justified by development and conservation narratives [6,7,[42][43][44]. The neoliberal-oriented policy of privatizing commons is one tool for dispossession and capital accumulation in contemporary capitalism [42,45] 3 .…”
Section: Appropriation and In Situ Displacement: A Conceptual Frameworkmentioning
confidence: 99%
See 3 more Smart Citations